HIST1H1C Regulates Interferon-β and Inhibits Influenza Virus Replication by Interacting with IRF3 - Liu, Xiaokun; Yang, Cha; Hu, Yong; Lei, Erming; Lin, Xian; Zhao, Lianzhong; Zou, Zhong; Zhang, Anding; Zhou, Hongbo; Chen, Huanchun; Qian, Ping; Jin, Meilin (Frontiers in Immunology, 2017)
Influenza virus NS2 is well known for its role in vRNP (viral RNP) nuclear export; however, its function has not been fully understood. A recent study showed that NS2 might interact with HIST1H1C (H1C, H1.2). Histones have been found to affect influenza virus replication, such as the H2A, H2B, H3 and H4, but H1 has not been detected. Here, we found that H1C interacts with NS2 via its C-terminal in the nucleus and that H1C affects influenza virus replication. The H1N1 influenza virus replicates better in H1C knockout A549 cells compared to wild-type A549 cells, primarily because of the regulation of H1C on IFN-β. Further studies showed that the H1C phosphorylation mutant (T146A) decreases IFN-β, while H1C methylation mutants (K34A, K187A) increases IFN-β by releasing the nucleosome and promoting IRF3 binding to the IFN-β promoter. Interestingly, NS2 interacts with H1C, which reduces H1C-IRF3 interaction and results in the inhibition of IFN-β enhanced by H1C. In summary, our study reveals a novel function of H1C to regulate IFN-β and uncovers an underlying mechanism, which suggests H1C plays a role in epigenetic regulation. Moreover, our results suggest a novel mechanism for the influenza virus to antagonize the innate immune response by NS2.